2002
DOI: 10.21273/jashs.127.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Indian Mustard and Allyl Isothiocyanate Inhibit Sclerotium rolfsii

Abstract: ADDITIONAL INDEX WORDS. Brassica, southern blight, soilborne pathogen, biofumigation ABSTRACT. Allyl isothiocyanate (AITC) is the predominant isothiocyanate produced by damaged tissues of Indian mustard (Brassica juncea (L) Czerniak). This study investigated Indian mustard and AITC mediated suppression of mycelial growth and sclerotial germination of Sclerotium rolfsii Saccardo, a common soilborne pathogen. Indian mustard (IM) treatments of 0, 0.1, 0.2, 0.6, 1.0, 2.0, 4.1, 5.1, 10.2, 20.4, 40.8, 81.6, and 163.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 23 publications
(18 reference statements)
2
19
0
Order By: Relevance
“…Pfender & D.J. Hagedorn (Smolinska et al 1997), Sclerotium rolfsii (Harvey et al 2002), and Fusarium sambucinum Fuckel (Mayton et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Pfender & D.J. Hagedorn (Smolinska et al 1997), Sclerotium rolfsii (Harvey et al 2002), and Fusarium sambucinum Fuckel (Mayton et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, AITC is suppressive to many species of fungi (Charron & Sams, 1999;Harvey et al, 2002;Mayton et al, 1996). Benzyl ITC and 3-methylsulWnylpropyl ITC suppressed 100% of A. alternata growth at concentrations of 0.55 and 1.2 mg/ml, respectively (Manici et al, 1997).…”
Section: Alternaria Response To Itcs In Vitromentioning
confidence: 99%
“…It had been found that isothiocyanates can be toxic to fungi (Charron & Sams, 1999;Harvey, Hannahan, & Sams, 2002;Smolinska, Morra, Knudsen, & James, 2003), bacteria (Delaquis & Mazza, 1995), nematodes and insects (Kermanshai et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, results from a number of studies indicated that the content of glucosinolates in the biofumigant material did not predict the biocidal activity (Angus et al, 1994;Bending & Lincoln, 1999;Charron & Sams, 1999;Harvey, Hannahan, & Sams, 2002;Lazzeri & Manici, 2001;McLeod & Steel, 1999;Morra & Kirkegaard, 2002). One reason for this apparent discrepancy could be that the conversion of glucosinolates into the biocidal ITCs is low.…”
Section: Brassica Biofumigation Mechanismmentioning
confidence: 99%